THE GENERAL COMPOSITION OF FINANCIAL INTERMEDIARIES. BANKS. THEIR MAIN FUNCTIONS - Xodjimamedov A.A; Sayfiddinova Shaxzoda Najmiddin qizi (TADQIQOTLAR, 2026)
ABSTRACT This article examines the general composition of financial intermediaries, with a specific focus on banks and their main functions within the financial system. Financial intermediaries play a critical role in mobilizing savings and allocating capital efficiently across the economy. Banks, as the primary financial intermediaries, facilitate economic growth by providing essential services such as deposit acceptance, credit provision, and payment processing. The study explores the structural components of financial intermediaries and analyzes how banks operate to support economic stability and development.